INDEPENDENSI KEKUASAAN KEHAKIMAN HUKUM ACARA MAHKAMAH KONSTITUSI: Independensi, Kekuasaan Kehakiman, Mahkamah Konstitusi - Nur Indra Socawibawa; Arif Wibowo (Jurnal Penelitian Multidisiplin, 2023)
One important factor in the amendment to the 1945 Constitution of the Republic of Indonesia is the existence of the Constitutional Court as a state institution whose function is to settle a number of cases in the field of constitutional law. country. The constitution must be implemented responsibly, in accordance with the will of the people and the ideals of democracy. The constitutional authority of the Constitutional Court is to carry out the principle of checks and balances which places all state institutions in the same position to have a balance in the administration of the state. The existence of the Constitutional Court is a real step forward in the joint regulation of the functioning of federal agencies. The Constitutional Court in administering its judiciary to consider, adjudicate and decide cases, always refers to the principle of administering justice, which is carried out simply and quickly.